Preparation method of Ni-based catalyst for hydrogen production through ammonia decomposition
Ni-Zr(1-x)CexOy catalyst was prepared by the double titration precipitation method, and the ratio of Ce3+ and Zr3+ was adjusted, which solved the problems of insufficient catalytic activity of existing Ni-based catalysts and complex preparation processes, and achieved efficient ammonia decomposition and hydrogen production performance and long-term stability.
Patent Information
- Application Number
- CN202411611907.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-25
AI Technical Summary
The existing Ni-based catalysts have insufficient catalytic activity in ammonia decomposition hydrogen production reaction, and the preparation process is complicated, making it difficult to effectively regulate the interaction between active metals and support.
Ni-Zr(1-x)CexOy catalyst was prepared by double titration precipitation method, the ratio of Ce3+ and Zr3+ was adjusted, the dispersion of metal particles and the exposure of active sites were controlled, and the interaction between metal and support was enhanced.
The ammonia decomposition hydrogen production performance of Ni-based catalysts is significantly improved, catalytic activity and long-term stability are enhanced, and the preparation process is simplified.
Smart Images

Figure CN119500160A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of hydrogen energy and relates to a method for preparing a Ni-based catalyst for producing hydrogen by decomposing ammonia. Background Art
[0003] Ammonia decomposition hydrogen production technology is a green and efficient method of hydrogen production because it does not generate harmful products, has high energy density and is more convenient to transport. Ammonia decomposition hydrogen production usually has a high reaction temperature, and it is necessary to prepare cheap and highly active catalysts to improve reaction efficiency and reduce reaction temperature.
[0004] Ru-based catalysts are the most active ammonia decomposition catalysts, but they are difficult to apply on a large scale due to their high price. Ni-based catalysts with low cost and high catalytic activity are very attractive as substitutes for Ru-based catalysts. Chinese patent CN118634820A discloses a method for preparing a catalyst with Ni as an active metal and ZrO2 as a carrier, which effectively reduces the reaction temperature of ammonia decomposition to produce hydrogen. Ni is expected to be widely used as an active metal for ammonia decomposition to produce hydrogen. In order to further improve the catalytic ability of Ni-based catalysts, the number of active sites of Ni, the bond-breaking ability of Ni-N bonds, etc. can be affected by designing a suitable carrier and utilizing the interaction between the metal and the carrier. Chinese patent CN114534736B discloses a method for preparing a catalyst by using a citric acid sol-gel method to prepare a carrier and using an isovolumetric impregnation method to load the active component Ni. This method modifies the LaAlO3 carrier by introducing the rare earth element Ce, thereby promoting the synergistic effect between the metal and the carrier, so that ammonia is better decomposed on the active metal surface. However, the preparation process of this method is complicated, the calcination temperature is high during the preparation of the carrier, and the interaction ability between the metal and the carrier is not significantly improved. The active metal cannot be effectively regulated. New processes are urgently needed to achieve Ni-based catalysts with stronger synergistic effects between the carrier and the active metal and simpler preparation processes, so as to further improve the ammonia decomposition and hydrogen production performance of Ni-based catalysts.
[0005] In order to solve the above problems, the present invention develops a method for preparing a Ni-based catalyst for hydrogen production by decomposing ammonia. Summary of the invention
[0006] The technical problem to be solved by the present invention is to further improve the interaction between the metal and the carrier by retaining the advantages of more exposed active sites of the impregnation method, controlling the dispersion of metal particles, and then improving the effect of the catalyst on hydrogen production by decomposing ammonia. The present invention provides a method for preparing a Ni-based catalyst for hydrogen production by decomposing ammonia.
[0007] The technical solution of the present invention:
[0008] A method for preparing a Ni-based catalyst for hydrogen production by decomposing ammonia comprises the following steps:
[0009] 1) mixing a metal cerium salt and a metal zirconium salt with deionized water in a certain proportion to obtain a metal ion mixed solution, and adding a metal nickel salt to a certain amount of deionized water to obtain a metal nickel salt solution;
[0010] 2) preparing a double alkaline solution containing hydroxide and carbonate as a precipitant;
[0011] 3) slowly dripping the metal nickel salt solution and the precipitant into the metal ion mixed solution by double titration, adjusting the pH to a certain range, reacting in an oil bath at a certain temperature to obtain a reaction product;
[0012] 4) The reaction product is washed with water and ethanol, dried, and calcined to obtain a Ni-based catalyst for decomposing ammonia.
[0013] In step 1), the sum of the molar amounts of cerium and zirconium metal ions remains unchanged, and the obtained Ni-Zr (1-x) Ce x O y In the catalyst, x=0.1-0.9, the total metal ion concentration in the metal ion mixed solution is 2-5 mol / L, and the concentration of the metal nickel salt solution is 0.05-0.1 mol / L. The metal cerium salt includes cerium nitrate, cerium chloride, and cerium sulfate, the metal zirconium salt includes zirconium nitrate, zirconium chloride, and zirconium sulfate, and the metal nickel salt includes nickel nitrate, nickel chloride, and nickel sulfate.
[0014] In step 2), the precipitant includes a mixed solution of sodium hydroxide and sodium carbonate or a mixed solution of ammonia and ammonium carbonate, with a concentration of 2 to 2.5 mol / L, wherein CO3 2- With OH - The molar ratio of is 1:1 to 1:1.25;
[0015] In step 3), the volume ratio of the metal nickel salt solution, the precipitant, and the metal ion mixed solution is 1.6:1:1, the pH value of the solution is adjusted to 9.0-10.0, the reaction temperature is 70-90° C., and the reaction time is 2-4 hours;
[0016] In step 4), the filtrate is washed with deionized water until the pH value of the filtrate is 7.0, the drying temperature is 70-90° C., the drying time is 12-16 hours, the roasting temperature is 400-500° C., and the roasting time is 2-4 hours.
[0017] The mass percentage of Ni in the nickel-based ammonia decomposition hydrogen production catalyst is 10% to 30%.
[0018] Beneficial effects of the present invention:
[0019] (1) The present invention provides a method for preparing a Ni-based catalyst for hydrogen production by decomposing ammonia. By different precipitation rates, during the precipitation of cerium-zirconium, part of the active metal Ni is precipitated on the surface of the cerium-zirconium precipitate, and part of it is precipitated together with the cerium-zirconium precipitate to form a mixture, and finally a Ni / Zr catalyst is obtained. (1-x) Ce x O y and NiZr (1-x) Ce x O y The catalyst structure between the two ensures that the active metal is both highly dispersed on the carrier surface and in a bulk phase combined with the carrier. This catalyst can ensure that the metal has highly exposed active sites while enhancing the interaction between the metal and the carrier, thereby significantly enhancing the ability of Ni-based catalysts to decompose NH3.
[0020] (2) The present invention adjusts the Ce content in the metal ion solution 3+ and Zr 3+ The ratio of was used to prepare a catalyst with strong interaction between metal and carrier, good metal dispersion and not easy to sinter. This type of catalyst showed excellent catalytic activity in the ammonia decomposition reaction to produce hydrogen. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The activity diagram of ammonia decomposition to hydrogen production of the catalysts prepared in Examples 1-5.
[0022] Figure 2 This is a graph of the long-term stability of the catalyst of Example 2.
[0023] Figure 3 This is the cyclic stability diagram of Example 2. DETAILED DESCRIPTION
[0024] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and technical solutions.
[0025] Example 1
[0026] A method for preparing a Ni-based catalyst for hydrogen production by decomposing ammonia, the method comprising the following steps:
[0027] (1) adding 2.17 g of cerium nitrate and 3.41 g of zirconium nitrate to 25 mL of deionized water and mixing them evenly to obtain a mixed solution, and adding 0.59 g of nickel nitrate to 25 mL of deionized water and completely dissolving them to obtain a nickel nitrate solution;
[0028] (2) 2.01 g of sodium hydroxide and 5.25 g of sodium carbonate were added to 25 mL of deionized water to dissolve to prepare a precipitant, and the nickel nitrate solution and the precipitant were slowly added to the cerium-zirconium mixed solution by double titration, the pH of the solution was adjusted to about 9.0, and the mixture was stirred in an oil bath at 80° C. for 4 h to obtain a reaction product;
[0029] (3) The reaction product was washed with deionized water and ethanol until the pH of the filtrate was 7.0, dried in an oven at 80°C for 16 h, and calcined at 400°C for 4 h in an air atmosphere to obtain a nickel-based catalyst Ni-Zr5Ce5O y .
[0030] Example 2
[0031] (1) adding 3.04 g of cerium nitrate and 1.29 g of zirconium nitrate to 25 mL of deionized water and mixing them evenly to obtain a mixed solution, and adding 0.59 g of nickel nitrate to 25 mL of deionized water and completely dissolving them to obtain a nickel nitrate solution;
[0032] (2) 2.01 g of sodium hydroxide and 5.25 g of sodium carbonate were added to 25 mL of deionized water to dissolve to prepare a precipitant, and the nickel nitrate solution and the precipitant were slowly dripped into the cerium-zirconium mixed solution, the pH was adjusted to about 9.0, and the mixture was stirred in an oven at 80° C. for 2 h to obtain a reaction product;
[0033] (3) The reaction product was washed with deionized water and ethanol until the pH of the filtrate was 7.0, dried in an oven at 80°C for 12 h, and calcined at 400°C for 2 h in an air atmosphere to obtain a nickel-based catalyst Ni-Zr3Ce7O y .
[0034] Example 3: The conditions are the same as in Example 1, except that cerium nitrate is changed to 3.04 g and zirconium nitrate is changed to 3.01 g to obtain a nickel-based catalyst Ni-Zr7Ce3O y .
[0035] Example 4: The conditions are the same as in Example 1, except that cerium nitrate is changed to 3.91 g and zirconium nitrate is changed to 0.43 g to obtain a nickel-based catalyst Ni-Zr1Ce9O y .
[0036] Example 5: The conditions are the same as in Example 1, except that cerium nitrate is changed to 0.43 g and zirconium nitrate is changed to 3.86 g to obtain a nickel-based catalyst Ni-Zr9Ce1O y .
[0037] Example 6: The conditions are the same as in Example 1, except that the metal cerium salt is changed to 1.23 g cerium chloride and the metal zirconium salt is changed to 1.17 g zirconium chloride to obtain a nickel-based catalyst Ni-Zr5Ce5O y -Cl.
[0038] Example 7: The conditions are the same as those in Example 2, except that the metal cerium salt is changed to 2.02 g of cerium sulfate and the metal zirconium salt is changed to 1.78 g of zirconium sulfate to obtain a nickel-based catalyst Ni-Zr5Ce5O y -SO4.
[0039] Comparative Example 1
[0040] A nickel-based ammonia decomposition hydrogen production catalyst and a preparation method thereof, the preparation method comprising the following steps:
[0041] 1. Take 3.04g of cerium nitrate, 1.29g of zirconium nitrate and 0.59g of nickel nitrate and add them to 25mL of deionized water and mix them evenly to obtain a mixed solution.
[0042] 2. Take 2.01g of sodium hydroxide and add it to 25mL of deionized water to dissolve to prepare a precipitant. Slowly drop the mixed solution into the precipitant, adjust the pH to 9.0, and stir in an oil bath at 80°C for 4h to obtain a reaction product.
[0043] 3. The reaction product was washed with deionized water and ethanol until the pH of the filtrate was 7.0, dried in an oven at 80°C for 16 h, and calcined at 400°C for 4 h in an air atmosphere to obtain a nickel-based catalyst Zr3Ce7O y / Ni.
[0044] Comparative Example 2
[0045] A nickel-based ammonia decomposition hydrogen production catalyst and a preparation method thereof, the preparation method comprising the following steps:
[0046] 1. Take 3.04g of cerium nitrate, 1.29g of zirconium nitrate and 0.59g of nickel nitrate and add them to 25mL of deionized water and mix them evenly to obtain a mixed solution.
[0047] 2. Take 2.01g of sodium hydroxide and add it to 25mL of deionized water to dissolve to prepare a precipitant, slowly drop the precipitant into the above mixed solution, adjust the pH to 11.0, stir in an oil bath at 80°C for 4h to obtain a reaction product;
[0048] 3. The reaction product was washed with deionized water and ethanol until the pH of the filtrate was 7.0, dried in an oven at 80°C for 16 h, and calcined at 400°C for 4 h in an air atmosphere to obtain a nickel-based catalyst NiZr3Ce7O y .
[0049] Comparative Example 3
[0050] A nickel-based ammonia decomposition hydrogen production catalyst and a preparation method thereof, the preparation method comprising the following steps:
[0051] 1. Take 3.04 g of cerium nitrate and 1.29 g of zirconium nitrate and add them to 25 mL of deionized water and mix them evenly to obtain a mixed solution;
[0052] 2. Take 2.01g of sodium hydroxide and 5.25g of sodium carbonate and add them to 25mL of deionized water to dissolve to prepare a precipitant, slowly drop the precipitant into the above mixed solution, adjust the pH to 9.0, stir in an oil bath at 60°C for 24h to obtain a reaction product;
[0053] 3. The reaction product was washed with deionized water until the pH of the filtrate was 7.0, dried in an oven at 80°C for 16 h, and calcined at 600°C for 4 h in an air atmosphere to obtain the catalyst carrier Zr3Ce7O y ;
[0054] 4. Add 0.59g Ni(NO3)2·4H2O to 40ml deionized water and stir to dissolve. Add 1g catalyst carrier and stir for 6h at 80℃ to obtain the reaction product. Calcined at 400℃ for 4h in air atmosphere to obtain nickel-based catalyst Ni / Zr3Ce7O y .
[0055] Test Example 1
[0056] Take a catalyst with a particle size of 60-80 mesh, the loading amount is 0.2g, the hydrogen pretreatment conditions are 400℃ reduction for 2h, and the hydrogen space velocity is 10,000mL / (g·h). The catalytic reaction temperature is 560℃, the raw gas is pure ammonia, the space velocity is 15,000mL / (g·h), the tail gas is detected and analyzed by gas chromatograph GC7900, and the catalytic activity is determined by the conversion rate of ammonia decomposition. The ammonia decomposition catalytic effect of the catalysts prepared in the above Examples 1-10 and Comparative Examples 1-3 was measured, and the corresponding measurement results are shown in Table 1:
[0057] Table 1 Ammonia decomposition activity test results
[0058] index Ammonia conversion rate (%) Example 1 94.3 Example 2 99.2 Example 3 92.6 Example 4 88.3 Example 5 89.8 Example 6 90.0 Example 7 88.9 Comparative Example 1 80.5 Comparative Example 2 75.2 Comparative Example 3 75.6
[0059] Table 1 and Figure 1 The results show that the activity of the catalyst of the present invention is better than that of the bulk catalyst of active metal mixed with metal oxide, because the catalyst of the present invention adopts double titration precipitation method to produce a supported structure, so that more active metal sites are exposed, which is beneficial to the decomposition reaction of ammonia; the activity of the catalyst of the present invention is better than that of supported Ni catalyst, because it has a bulk structure of active metal mixed with oxide, and has a strong metal-support interaction, which is beneficial to Ce in oxide. 3+The oxygen vacancies provide electrons for the active metal Ni, thereby promoting the dissociation and desorption of NH3 on the catalyst surface, and the ammonia decomposition catalytic effect is better. The catalyst of the present invention has two structures at the same time, combining the advantages of both, and realizes the complete conversion of ammonia at a lower temperature. The activity order of the catalyst of the present invention is: Ni / Zr3Ce7O y >Ni / Zr7Ce3O y >Ni / Zr5Ce5O y >Ni / Zr1Ce9O y >Ni / Zr9Ce1O y , and among them Ni / Zr3Ce7O x The catalyst has the best catalytic activity. When the ammonia space velocity is 15,000 mL / (g·h), the ammonia conversion rate is 99.2% at 560°C.
[0060] Test Example 2
[0061] Take a catalyst with a particle size of 60-80 mesh, the loading amount is 0.2g, the hydrogen pretreatment conditions are 400℃ reduction for 2h, and the hydrogen space velocity is 10,000mL / (g·h). The catalytic reaction temperature is 560℃, the raw gas is pure ammonia, the space velocity is 18,000mL / (g·h), the tail gas is detected and analyzed by gas chromatograph GC7900, and the catalytic activity is determined by the conversion rate of ammonia decomposition. The ammonia decomposition catalytic effect of the catalysts prepared in the above Examples 1-10 and Comparative Examples 1-3 was measured, and the corresponding measurement results are shown in Table 2:
[0062] Table 2 Ammonia decomposition activity test results
[0063] index Ammonia conversion rate (%) Example 1 92.2 Example 2 98.0 Example 3 90.7 Example 4 87.1 Example 5 88.4 Example 6 87.8 Example 7 85.6 Comparative Example 1 75.0 Comparative Example 2 73.7 Comparative Example 3 74.4
[0064] The results in Table 2 show that the Ni-based catalyst of the present invention still has good catalytic activity under the reaction conditions of increasing ammonia space velocity, wherein the activity order of the catalyst is: Ni / Zr3Ce7O y >Ni / Zr7Ce3O y >Ni / Zr5Ce5O y >Ni / Zr1Ce9O y >Ni / Zr9Ce1O y , where Ni / Zr3Ce7AlO x The catalyst has the best catalytic activity. When the ammonia space velocity is 18,000 mL / (g·h), the ammonia conversion rate is 98.0% at 560°C.
[0065] Test Example 3
[0066] Take a catalyst with a particle size of 60-80 mesh, the loading amount is 0.2g, the hydrogen pretreatment conditions are 400℃ reduction for 2h, and the hydrogen space velocity is 10,000mL / (g·h). The catalytic reaction temperature is 560℃, and the reaction is repeated 5 times. The raw gas is pure ammonia, the space velocity is 15,000mL / (g·h), and the tail gas is detected and analyzed by gas chromatograph GC7900. The catalytic activity is determined by the conversion rate of ammonia decomposition. The ammonia decomposition catalytic effect of the catalyst prepared in Example 2 above is measured, and the corresponding measurement results are shown in Table 3:
[0067] Table 35 Cycle Stability Test Ammonia Decomposition Activity Test Results
[0068] index Ammonia conversion first 99.0 Second time 98.8 The third time 98.6 Fourth 98.6 Fifth 98.4
[0069] Test Example 4
[0070] Take a catalyst with a particle size of 60-80 mesh, the loading amount is 0.2g, the hydrogen pretreatment conditions are 400℃ reduction for 2h, and the hydrogen space velocity is 10,000mL / (g·h). The catalytic reaction temperature is 560℃, the continuous evaluation is 30h, the raw gas is pure ammonia, the space velocity is 15,000mL / (g·h), the tail gas is detected and analyzed by gas chromatograph GC7900, and the catalytic activity is determined by the conversion rate of ammonia decomposition. The ammonia decomposition catalytic effect of the catalysts prepared in the above Examples 1-4 and Comparative Examples 1-3 was measured, and the corresponding measurement results are shown in Table 4:
[0071] Table 4 Ammonia decomposition activity test results before and after 30h stability test
[0072]
[0073]
[0074] Table 3, Table 4 and Figure 2 , Figure 3 The results show that the nickel-based catalyst of the present invention has no obvious deactivation in 560°C, 5 cycle stability tests and 30h stability tests. This is because the active metal is highly dispersed and the interaction between the metal and the carrier is strong. The active metal is not easy to agglomerate at high temperature, so it has excellent long-term stability and cycle stability.
[0075] Obviously, the above examples are only examples for clear explanation, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the invention.
Claims
1. A method for preparing a Ni-based catalyst for hydrogen production by decomposing ammonia, characterized in that: The steps include: 1) mixing a metal cerium salt and a metal zirconium salt with deionized water in a certain proportion to obtain a metal ion mixed solution, and adding a metal nickel salt to the deionized water to obtain a metal nickel salt solution; 2) preparing a double alkaline solution containing hydroxide and carbonate as a precipitant; 3) slowly dripping the metal nickel salt solution and the precipitant into the metal ion mixed solution by double titration, adjusting the pH to a certain range, reacting in an oil bath at a certain temperature to obtain a reaction product; 4) The reaction product is washed with water and ethanol, dried, and calcined to obtain a Ni-based catalyst for hydrogen production by decomposing ammonia.
2. The preparation method according to claim 1, characterized in that: In step 1), the sum of the molar amounts of cerium and zirconium metal ions remains unchanged, and the obtained Ni-Zr (1-x) Ce x O y In the catalyst, x=0.1-0.9, the total metal ion concentration in the metal ion mixed solution is 2-5 mol / L; the concentration of the metal nickel salt solution is 0.05-0.1 mol / L; the metal cerium salts include cerium nitrate, cerium chloride, and cerium sulfate; the metal zirconium salts include zirconium nitrate, zirconium chloride, and zirconium sulfate; and the metal nickel salts include nickel nitrate, nickel chloride, and nickel sulfate.
3. The preparation method according to claim 1, characterized in that: In step 2), the precipitant includes a mixed solution of sodium hydroxide and sodium carbonate, or a mixed solution of ammonia water and ammonium carbonate, with a concentration of 2 to 2.5 mol / L, wherein CO3 2- With OH - The molar ratio is 1:1 to 1:1.
25.
4. The preparation method according to claim 1, characterized in that: In step 3), the volume ratio of the metal nickel salt solution, the precipitant, and the metal ion mixed solution is 1.6:1:1, the pH is 9.0-10.0, the reaction temperature is 70-90° C., and the reaction time is 2-4 hours.
5. The preparation method according to claim 1, characterized in that: In step 4), the filtrate is washed with deionized water until the pH value of the filtrate is 7.0, the drying temperature is 70-90° C., the drying time is 12-16 hours, the calcination temperature is 400-500° C., and the calcination time is 2-4 hours.
6. The preparation method according to claim 1, characterized in that: The mass percentage of Ni in the Ni-based catalyst is 10% to 30%.
Citation Information
Patent Citations
A perovskite catalyst for ammonia decomposition, its preparation method and application
CN114534736B
Preparation method of supported Ni-based ammonia decomposition catalyst as well as product and application of supported Ni-based ammonia decomposition catalyst
CN118634820A
Cited By
Method for producing hydrogen through ammonia decomposition based on cerium dioxide reverse catalyst
CN121513890A